Retrotransposons as a Source of DNA Damage in Neurodegeneration - Peze-Heidsieck, Eugenie; Bonnifet, Tom; Znaidi, Rania; Ravel-Godreuil, Camille; Massiani-Beaudoin, Olivia; Joshi, Rajiv L.; Fuchs, Julia (Frontiers in Aging Neuroscience, 2022)
The etiology of aging-associated neurodegenerative diseases (NDs), such as Parkinson disease (PD) and Alzheimer’s disease (AD), still remains elusive and no curative treatment is available. Age is the major risk factor for PD and AD, but the molecular link between aging and neurodegeneration is not fully understood. Aging is defined by several hallmarks, some of which partially overlap with pathways implicated in NDs. Recent evidence suggests that aging-associated epigenetic alterations can lead to the derepression of the LINE-1 (Long Interspersed Element-1) family of transposable elements (TEs), and that this derepression might have important implications in the pathogenesis of NDs. Almost half of the human DNA is composed of repetitive sequences derived from TEs and TE mobility participated in shaping the mammalian genomes during evolution. Although most TEs are mutated and no longer mobile, more than 100 LINE-1 elements have retained their full coding potential in humans and are thus retrotransposition-competent. Uncontrolled activation of TEs has now been reported in various models of neurodegeneration and in diseased human brain tissues. We will discuss in this review the potential contribution of LINE-1 elements in inducing DNA damage and genomic instability, which are emerging pathological features in NDs. TEs might represent an important molecular link between aging and neurodegeneration, and a potential target for urgently needed novel therapeutic disease-modifying interventions.